Assessing the effects of engagement with maternal ostensive signals in infants with neurodevelopmental risk - Teo, Joan Wei Ling (Nanyang Technological University, 2024)
Background. Social ostensive signals, such as gaze, gaze following, calling the infant’s name, gesture and smile, are communicative cues commonly observed during interactions between infants and caregivers to indicate intent to interact or convey information. While extensive research has documented how ostensive signals promote infants’ cognitive development specifically in learning, language and social skills, the effects of these signals on infants with atypical neurodevelopmental trajectories remains unclear. Furthermore, there is limited understanding on whether engaging in ostensive signals provides any indication of or contributes to the development of executive functions (EF) such as working memory, inhibitory control and cognitive flexibility.